MANIFESTATIONS OF HETEROTOPIC OSSIFICATION IN PATIENTS WITH RADIAL HEAD FRACTURES COMBINED WITH FOREARM DISLOCATIONS - Matelenok, Yevgen (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Heterotopic ossifications (HO) is one from the negative consequences of the joint injuries, and they are especially significant for fractures and fracture-dislocations of the elbow, reaching 37 %. Objective. To study the frequency of occurrence and form of manifestation of HO in patients with fractures of the radial head (RH) in combination with dislocations of the forearm under the conditions of restoration of the head and the impossibility of its preservation. Methods. The study is based on a retrospective analysis of clinical observation material of 48 patients with dislocations of the forearm in combination with fractures of the RH, among which during surgical treatment in 39 patients the head of the radius was preserved (1st group), in 9 patients it was not possible to save the head (2nd group). Results. In 9 patients (23 %) of the 1st group and in 5 (56 %) of the 2nd group for an average period of 6 months, X-ray examination revealed manifestations of HO. Surgical interventions were performed later than 48 hours. It is noteworthy that among patients of the 1st group, HO, which caused limitation of the range of motion in the joint, occurred in 2 cases out of 9, that is, in 22 %, and among patients of the 2nd group, significantly more often — in 4 out of 5 patients, that is, in 80 % of cases. Differences between these indicators in groups are statistically significant (p < 0.05). The functional assessment of the elbow joints by the Mayo Clinic Score in groups was significantly higher in the patients of the 1st group — (87 ± 9) points compared to (49 ± 16) in the patients of the 2nd group (p < 0.05). Conclusions. In patients with fractures of the RH in combination with dislocations of the forearm in cases of impossibility of preserving the head, the formation of HO in the area of the elbow joint is observed more than twice as often compared to patients with preserved head (56 % vs. 23 %). HO of forms II and III are observed more than three times more often in patients with fractures of the RH in combination with dislocations of the forearm in cases of impossibility of preserving the head compared to cases of its restoration (80 % vs. 22 %). Given the high risk of HO in the elbow joint of patients with fractures of the RH in combination with dislocations of the forearm in case of impossibility of preserving the head, as well as in cases of postponement of the necessary surgical treatment for fractures in the elbow joint, it is necessary to take care of the available measures for the prevention of HO.